The polytypism of crystals of the mixed compound Cu(L-Ala)(L-Ser) - Diacon, Ion (D.Ghitu Institute of Electronic Engineering and Nanotechnologies, 2009)

(untitled)
Atomic structures of two polytypic modifications of crystals of mixed copper(II)